Seawater carbonate chemistry and transgenerational physiological and molecular data of Oryzias melastigma - Tzu-Yen Liu; Jia-Jiun Yan; Ying-Jey Guh; Oki Hayasaka; Li-Yih Lin; Pung-Pung Hwang; Guan-Chung Wu; Ming-Tsung Chung; Yung-Che Tseng (PANGAEA, 2025)
To understand the long-term and transgenerational effects of marine fish, we applied a marine model animal, Oryzias melastigma, to a CO2-induced acidified condition (pH 7.6). This study focused on the larvae extquotesingles physiological acclimation and how they face acidified stress through gene expression changes. Furthermore, we checked the epigenetic modifications, like DNA methylation, to know if there were any parental effects under this stress. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from Dryad (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-08-21.